Air-Layering through Sphagnum Moss in Elaeocarpus angustifolius Blume (Rudraksha)-Commercially Important Tree Species - Verma, Praveen Kumar; Das, Niren; Kumar, Vishavjit; Kaushik, Pawan. K.; Yadav, Alok (Indian Forester, 2016)
The present paper-deals with an easy air-layering method using two species of Sphagnum (S. papillosum and S. khasianum) as substrate media in commercially important Elaeocarpus angustifolius Blume. This substrate medium is easy to apply, time saving with minimal involvement of tools and further labour input, it also surpass many problems faced by other means of propagation.